Development of a measure quantifying helpful psychotherapy interventions: The Helpful Therapeutic Attitudes and Interventions Scale - Li, Xiaobao; Gu, Hong; Zhao, Xudong; Chen, Fazhan; Liu, Liang (Frontiers in Psychiatry, 2022)
Despite the number of empirical studies identifying the helpful factors correlated with beneficial psychotherapy outcomes, there is no validated scale that measures helpful therapeutic attitudes and interventions applied by therapists within the actual therapy process in China. In the current study, we developed the Helpful Therapeutic Attitudes and Interventions Scale (HTAIS) as an accessible client-rated instrument to measure useful interventions applied by the therapist during psychotherapy sessions. Based on the results of previous literature and our prior psychotherapy process studies, a 40-item measure was initially designed. Two studies with a total of 2780 Chinese participants who received psychotherapy were carried out to evaluate the structure, reliability, and validity of the developed scale. Principal component analysis yielded a three-component HTAIS containing 26 items. The scale included dimensions labeled “Empathy, respect and neutrality”, “Using techniques to solve practical issues” and “In-depth exploration and expansion”. Confirmatory factor analysis showed the construct validity of the derived three components model. And the developed scale had high internal consistency and test-retest reliability. The scale scores of the HTAIS were positively correlated with those of the Working Alliance Scale and Session Rating Scale, as well as clients’ perceived therapy efficiency and satisfaction, thus supporting its concurrent validity. The HTAIS allows an immediate examination, as experienced by the client, of the extent to which certain useful therapeutics interventions have been conducted during therapy and could help to improve the clinician’s subsequent therapy strategies. Future research is suggested to further validate the scale, especially to assess its psychometric properties in various populations with different clinical complaints.